Forty years of research on human resource management in family firms: analyzing the past; preparing for the future. Issue 3 (22nd July 2020) - Flamini, Giulia; Gnan, Luca; Pellegrini, Massimiliano Matteo
Abstract : Purpose: This paper explores the field of human resource management (HRM) in family firms, assessing the evolution of this research through a four-domain model that reflects the relationships between cognitions, actions and performances associated with organizational choices. Design/methodology/approach: The authors have performed a bibliometric review of 363 peer-reviewed papers from over the past four decades (1976–2016) in order to provide activity indicators for the overall phenomenon and systemize the entire body of literature into specific HRM strategy domains or practices, using a double-entered pivot table. Findings: The study framework provides managerial implications with regard to the HRM decisions made when attempting to improve human capital in family firms. Accordingly, the authors view HRM-centered decisions and strategies in family firms as ways to scan for and appraise contingent dimensions, make sense of the current environment, make good choices and achieve high performance levels. Originality/value: The authors offer this four-domain theoretical scheme as a framework through which the field can be interpreted, proposing some potential avenues for moving forward.